Developing learning tools based on merdeka curriculum for the Sleman regency early childhood education forum - Nur Cholimah; Eka Sapti Cahya Ningrum; Martha Christianti; Ika Budi Maryatun (Community Empowerment, 2024)
This community service initiative aimed to enhance the capacity of early childhood education (PAUD) teachers in developing learning tools aligned with the Merdeka Curriculum. The program involved training on crafting Merdeka Curriculum-based teaching materials. The participants were PAUD teachers from the Sleman Regency Early Childhood Education Forum (Forum PAUD). The activities unfolded in several phases: pre-test, mentoring, practice in creating teaching materials, and post-test. The outcomes revealed that 85.3% of the teachers were now capable of creating and developing teaching modules, even implementing them in their schools. The utilization of loose parts also witnessed an increase, with only 12.1% of teachers not yet incorporating loose parts as a learning resource under the Merdeka Curriculum.